Rare and aggressive: imaging insights of intraperitoneal and retroperitoneal rhabdomyosarcoma in children and young adults - Santra, Shreyosi; Arora, Suryansh (International Journal of Contemporary Pediatrics, 2025)
This case series presents two cases of rhabdomyosarcoma (RMS), a rare malignancy of mesenchymal origin that accounts for 5% of all paediatric cancers and is extremely rare to present in adults. It can develop in various sites, including the head and neck, thorax, liver, biliary tract, retroperitoneum, urinary bladder, vagina, extremities, and paratesticular locations. Herein we present a case series of intrabdominal RMS, comprising the first case, an intraperitoneal RMS in a 2-year-old male child, and the second case, a retroperitoneal RMS in a 22-year-old male. Intraperitoneal RMS is extremely rare. Intraperitoneal and retroperitoneal RMS are aggressive tumours and have a poor prognosis. Both cases were of the spindle cell type of RMS, which is the most uncommon type.